2008
DOI: 10.1038/onc.2008.342
|View full text |Cite
|
Sign up to set email alerts
|

LKB1; linking cell structure and tumor suppression

Abstract: Germ line mutations in the LKB1 tumor suppressor gene are associated with the Peutz-Jeghers polyposis and cancer syndrome. Somatic mutations in Lkb1 are observed in sporadic pulmonary, pancreatic and biliary cancers and melanomas. The LKB1 serine-threonine kinase functionally and biochemically links control of cellular structure and energy utilization through activation of the AMPK family of kinases. Lkb1 regulates cell polarity through downstream kinases including AMPKs, MARKs and BRSKs, and nutrient utilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
164
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(174 citation statements)
references
References 118 publications
(141 reference statements)
6
164
0
Order By: Relevance
“…Liver kinase B1 (LKB1) is a tumor suppressor gene whose inactivating mutations are implicated in various sporadic cancers and are responsible for the majority of Peutz-Jeghers syndrome cases (1)(2)(3)(4)(5). Expression of LKB1 is ubiquitous in many cell types and tissues, and its high expression in fetal tissues is consistent with the critical role of LKB1 in embryonic development (6 -9).…”
mentioning
confidence: 97%
“…Liver kinase B1 (LKB1) is a tumor suppressor gene whose inactivating mutations are implicated in various sporadic cancers and are responsible for the majority of Peutz-Jeghers syndrome cases (1)(2)(3)(4)(5). Expression of LKB1 is ubiquitous in many cell types and tissues, and its high expression in fetal tissues is consistent with the critical role of LKB1 in embryonic development (6 -9).…”
mentioning
confidence: 97%
“…Although AMPK, Sik2 and Mark2 have been proposed as major proximate regulators for Crtc2 (Lizcano et al, 2004;Dentin et al, 2007;Fu and Screaton, 2008;Hezel and Bardeesy, 2008), Sik1 has also been suggested as an important kinase inhibitor for Crtc1 transcriptional activity (Katoh et al, 2006). Further, SIK1 is a Crtc1/ cAMP/CREB target gene whose induction is proposed to phosphorylate and mediate a negative feedback loop on Crtc1 in neuronal cells .…”
Section: Discussionmentioning
confidence: 99%
“…Par4 is an established tumor suppressor, a substrate of aPKC and a master kinase, which phosphorylates Par1 and AMP activated protein kinase (AMPK/PKA), involved in a parallel polarity pathway important under conditions of energetic stress (Lee et al, 2007;Mirouse et al, 2007) (see Hezel and Bardeesy, 2008). Activation of Par4 promotes the polarization of intestinal epithelial cells in the absence of cell-cell contacts (Baas et al, 2004a).…”
Section: Domain-identity Machinerymentioning
confidence: 99%
“…Mutations in the tumor suppressor Par4 (LKB1), a kinase for AMPK, and a major inducer of cell polarity when activated, lead to the hereditable Peutz-Jeghers cancer syndrome, characterized by predisposition to a variety of rare intestinal cancer and other types of cancer (Wodarz and Nathke, 2007) (see Hezel and Bardeesy, 2008). The lipid phosphatase PTEN is also considered a tumor suppressor and controls the recruitment of the Par complex to the apical PM either directly or through the generation of PIP2 (MartinBelmonte et al, 2007).…”
Section: Hijacking Of the Domain-identity Machinerymentioning
confidence: 99%